P397 Effectiveness of vedolizumab (VDZ) for the induction of remission in inflammatory bowel disease (IBD): Results from the Spanish Eneida Registry. (16th January 2018) - Chaparro, M; Garre, A; Alfaro, I; Iborra, M; Mesonero, P; Vera Mendoza, I; Rodríguez, A; Miquel-Cusachs, J; Riestra, S; Navarro, P; De Castro Parga, L; González-Muñoza, C; et al.
Abstract: Background: The aims of this study were (1) to assess the effectiveness of VDZ in IBD patients and (2) to identify factors associated with the response to the treatment. Methods: IBD patients [Crohn's disease (CD) and ulcerative colitis (UC)] that had received at least 3-induction doses with VDZ in the ENEIDA registry—a large prospectively maintained Spanish database promoted by the Spanish Working Group in Crohn's and Colitis (GETECCU) were included. Patients treated with VDZ due to active IBD [Partial Mayo Score (PMS) ≥2 or Harvey-Bradshaw (HBI) >4] were included. Short-term response was evaluated at week 14. Clinical response was defined as reduction in the PMS ≥3 points and a decrease of at least 30% from baseline, with a decrease of ≥1 point on the rectal bleeding subscale. For luminal CD, partial response was defined as a decrease in the HBI ≥3 points without reaching remission. Severity of the disease was rated by PMS or HBI. The variables associated with short-term remission were identified by logistic regression model. Results: A total of 274 patients were included; 144 (52%) of them had CD (Table 1). A total of 257 patients (94%) had been refractory to biologic agents before starting VDZ: 60 patients (22%) had previously failed to a biologic agent, and 197 (71%) to at least 2 anti-TNF drugs. After the induction doses (week 14), 66% of patients responded to the treatment (48% achieved remission and 18% partial response). The proportion of patients that reached remission was significantly higher among those naïve to anti-TNF drugs vs. those receiving VDZ after one anti-TNF vs. those receiving VDZ after at least two anti-TNFs (82 vs. 52 vs. 45%, respectively, p < 0.05). In addition, remission at week 14 was significantly lower among patients with severe disease at VDZ starting in comparison with those with moderate or mild disease (28 vs. 40. vs. 70%, respectively, p < 0.001). In the multivariate analysis, to have CD (vs. UC), the number of previous anti-TNF treatments and the severity of the disease were associated with lower probability of achieving remission at week 14 (Table 2). Conclusions: Approximately 2/3 of patients respond to VDZ treatment, and 1/2 reach remission, even in a refractory IBD cohort. To have CD (instead of UC), previous failure to at least 2 anti-TNF drugs and severe disease activity at VDZ starting were significantly associated with lower probability of remission at week 14.